Nickel particles and method for producing nickel particles
By forming an alloy region between nickel and metal element M on the surface of nickel particles, the problem of insufficient sintering resistance and high resistance in the prior art is solved, and the effect of improving sintering resistance and reducing resistance in a multi-layer ceramic capacitor is achieved.
Patent Information
- Application Number
- CN202380063344.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-06-28
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-06-28
AI Technical Summary
The prior art is difficult to prevent defects due to different sintering temperatures by improving the sintering resistance of nickel particles in a multi-layer ceramic capacitor without increasing the resistance of the internal electrodes.
By forming an alloy region containing nickel and metal element M (such as tin or zinc) on the surface of nickel particles, the content and distribution of metal element M are controlled to improve the sintering resistance of nickel particles while maintaining low resistance.
It is achieved to improve the sintering resistance of nickel particles without increasing resistance, reduce the temperature difference between the internal electrode and the dielectric layer during the sintering process, and prevent the occurrence of cracks and layered defects.
Smart Images

Figure CN119816387A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to nickel particles and a method for producing the same. Background Art
[0002] Nickel particles are generally used to form the internal electrodes of multilayer ceramic capacitors (hereinafter also referred to as "MLCC") used in electronic devices. In the manufacture of MLCC, when the internal electrodes containing nickel particles and the laminated body of the dielectric layer are fired simultaneously, defects may occur in the internal electrodes due to the difference in the sintering temperature of the raw materials. In order to prevent such undesirable situations, it is required to improve the sintering resistance of nickel particles.
[0003] For example, Patent Document 1 discloses a technology that uses nickel powder containing tin or zinc obtained by PVD or CVD to form internal electrodes of MLCC. The document states that by adding non-magnetic metals such as tin to nickel powder, the crystal structure of nickel is distorted, thereby increasing the sintering temperature of the nickel powder.
[0004] Patent Document 2 discloses a technique for using nickel powder having a substantially spherical particle shape and surface-treated with tin to form an internal electrode of an MLCC. In addition, the document discloses that zinc is used for surface treatment in addition to tin. The document states that the sintering behavior of the nickel powder described in the document is improved.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2014 / 080600 Pamphlet
[0008] Patent Document 2: Japanese Patent Application Publication No. 2018-104819 Summary of the invention
[0009] However, with the recent improvement in the performance of electronic devices, it is required to further prevent the adverse conditions caused by defects that may occur in the internal electrodes of MLCC. In order to meet this requirement, it is expected that the sintering resistance of nickel particles is further improved, and it is also expected that the resistance of the electrode will not be excessively increased when the nickel particles are used to form the internal electrodes.
[0010] Therefore, an object of the present invention is to provide nickel particles having high sintering resistance without excessively increasing electrical resistance.
[0011] The present invention provides a nickel particle having a surface region comprising an alloy of nickel and a metal element M,
[0012] The metal element M is at least one selected from tin and zinc,
[0013] The content of the metal element M relative to the total mass of the nickel particles is 0.16 mass % to 11.4 mass %,
[0014] When measuring the area from the outermost surface to the sputtering depth of 5 nm in terms of SiO2 in the depth direction of the above-mentioned nickel particles by X-ray photoelectron spectroscopy, in this area, the maximum value of the ratio of the number of atoms of the metal element M to the total number of atoms of the nickel element and the metal element M is set to X (at%), and when the above-mentioned nickel particles are measured by ICP emission spectroscopy, when the ratio of the number of atoms of the metal element M to the total number of atoms of the nickel element and the metal element M is set to Y (at%), the value of X / Y is 1.5 to 30.
[0015] The present invention also provides a method for producing nickel particles, which comprises heating a mixed solution containing nickel hydroxide particles, a polyol, polyvinyl pyrrolidone and polyethyleneimine to produce nickel particles.
[0016] 30 to 200 parts by mass of polyvinyl pyrrolidone is used per 1 part by mass of polyethyleneimine.
[0017] The nickel hydroxide particles are reduced to nickel mother particles by the heating.
[0018] The mixed solution is mixed with a compound of a metal element M while a portion of the nickel hydroxide particles remain, and the compound is reduced to metal M, thereby forming a surface region of an alloy containing nickel and the metal element M on the nickel mother particle.
[0019] The metal element M is at least one selected from tin and zinc. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of the nickel particles obtained in Example 3.
[0021] Figure 2 This is a scanning electron microscope image of the nickel particles obtained in Comparative Example 2. DETAILED DESCRIPTION
[0022] The present invention is described below based on its preferred embodiment. The nickel particles of the present invention have a nickel mother particle and a surface region of an alloy containing nickel and a metal element M (hereinafter also referred to as "nickel / metal M alloy") located on the surface of the mother particle. The "nickel mother particle" in this specification refers to a particle that is substantially composed of nickel elements and contains inevitable elements in the remainder. Inevitable elements include, for example, oxygen and carbon elements derived from oxygen and carbon dioxide in the atmosphere, and nitrogen elements that may be mixed in the manufacturing process of nickel particles.
[0023] The nickel mother particle in the nickel particle has a surface region containing a nickel / metal M alloy on its surface. In this specification, "nickel / metal M alloy" refers to a nickel-based alloy containing a metal element M described later. The nickel / metal M alloy is substantially composed of an alloy of a nickel element and a metal element M, and contains inevitable elements in the remaining part. In the surface region containing the nickel / metal M alloy, a portion of the metal element M may also exist in the state of a single substance of the metal element M (i.e., a metal state). Alternatively, a portion of the metal element M may also exist in the state of a compound of the metal element M. Alternatively, the metal element M may also exist in a state of combining them in two or more. In the case where the metal element M exists in the surface region containing the nickel / metal M alloy in the state of the above-mentioned metal element M compound, as the compound, for example, oxides, hydroxides, sulfides, sulfur oxides, borides, phosphides, etc. containing metal M can be listed, but are not limited to these. In particular, the metal element M in the surface region containing the nickel / metal M alloy substantially only contains an alloy with nickel. This matter is preferred from the viewpoint of maximizing the advantages originally possessed by the nickel particles of the present invention. In this specification, "substantially only contains an alloy with nickel" means the following: the metal element M other than the alloy with nickel contained in the above-mentioned surface area is intentionally excluded, and trace amounts of the metal element M alone or the metal element M compound inevitably mixed in the manufacturing process of the nickel particles are allowed.
[0024] The metal element M in the nickel particles is preferably at least one selected from tin and zinc. When the metal element M is tin or zinc, the sintering resistance can be further improved without excessively increasing the resistance of the nickel particles. The metal element M can use either tin or zinc, or both tin and zinc. In the following description, when the metal element M (or metal M) is mentioned, it refers to tin or zinc or both tin and zinc according to the context.
[0025] The fact that the nickel particles contain the nickel / metal M alloy in the surface region thereof can be confirmed by the following method.
[0026] Specifically, first, by measuring the nickel particles using X-ray photoelectron spectroscopy (hereinafter also referred to as "XPS"), it is confirmed that the nickel particles contain metal elements M in their surface regions, and that the metal elements M are mainly in a metallic state. Next, it is confirmed that the a-axis length in the X-ray diffraction peak of the above-mentioned nickel particles is elongated compared to the a-axis length in the X-ray diffraction peak obtained by pre-measurement of only the nickel particles. The elongation of the a-axis length in the X-ray diffraction peak means that a solid solution has occurred in the substance. Therefore, according to the presence of the metal element M in the surface region of the nickel particles in a metallic state confirmed by the measurement of XPS, and the presence of a solid solution of the metal element M and nickel confirmed by the comparison of the a-axis length, it can be confirmed that the nickel particles contain a nickel / metal M alloy in their surface region.
[0027] The proportion of the nickel particles containing the metal element M in their surface regions can be measured by XPS. In detail, when the region from the outermost surface to the sputtering depth of 5 nm in terms of SiO2 is measured by XPS in the depth direction of the nickel particles (hereinafter, the region is also referred to as the "particle surface region"), in the particle surface region, the maximum value of the ratio of the number of atoms of the metal element M to the total number of atoms of the nickel element and the metal element M, that is, the value of X is preferably 0.5 at% or more. The above-mentioned "maximum value" refers to the maximum value of the value of X when the values of multiple X measured along the thickness direction of the particle surface region are different. It is preferred that the metal element M exists in a manner having a portion with a value of X of 0.5 at% or more from the viewpoint of further improving the sintering resistance of the nickel particles described later. From the same viewpoint, the value (at%) of X is more preferably 0.5 at% or more, more preferably 1 at% or more, and more preferably 2 at% or more. In addition, from the same viewpoint, the value (at%) of X is more preferably 70 at% or less, more preferably 30 at% or less, and more preferably 20 at% or less. The method for measuring the value of X will be described in the examples described later.
[0028] The so-called "outermost surface of the nickel particle" mentioned above refers to the outermost surface of the nickel particle including the surface treatment agent when there is a surface treatment agent such as an organic acid or an amine on the surface of the nickel particle. When there is no surface treatment agent on the surface of the nickel particle, it refers to the surface of the particle itself.
[0029] The nickel particles preferably contain 0.16 mass % to 11.4 mass % of the metal element M relative to the entire nickel particles. When the content of the metal element M relative to the nickel particles is within this range, the sintering resistance can be further improved without excessively increasing the resistance of the nickel particles.
[0030] When the metal element M is tin, from the same viewpoint as above, the content of tin relative to the entire nickel particles is more preferably 0.3% by mass or more, more preferably 0.4% by mass or more, and further preferably 1% by mass or more. In addition, the content of tin relative to the entire nickel particles is more preferably 6% by mass or less.
[0031] When the metal element M is zinc, from the same viewpoint as above, the content of zinc relative to the entire nickel particles is more preferably 0.2% by mass or more, more preferably 0.4% by mass or more, and further preferably 0.5% by mass or more. In addition, the content of zinc relative to the entire nickel particles is more preferably 6.7% by mass or less, and more preferably 3.4% by mass or less.
[0032] The content of the metal element M relative to the entire nickel particles can be measured by ICP emission spectrometry as described below.
[0033] The nickel particles of the present invention are based on the condition that the content of the metal element M relative to the whole nickel particle satisfies the above range. In the whole nickel particle, the ratio of the number of atoms of the metal element M to the total number of atoms of the nickel element and the metal element M, that is, the value of Y (at%) is preferably 0.15at% to 6at%. The existence of the metal element M in such a way that the value of Y is within this range is preferred from the viewpoint of further improving the sintering resistance without excessively increasing the resistance of the nickel particles. From the same viewpoint, the value of Y is particularly preferably 0.2at% or more, and particularly preferably 0.5at% or more. In addition, the value of Y is particularly preferably 6at% or less, and particularly preferably 3at% or less.
[0034] The ratio of the number of atoms of the metal element M contained in the entire nickel particle, i.e., the value of Y, is measured by ICP emission spectrometry. Specifically, first, the entire nickel particle is measured by ICP emission spectrometry to determine the content ratio of the nickel element and the content ratio of the metal element M. Next, the content ratio (mass %) of the nickel element is divided by the atomic weight of the nickel element (58.7), and the content ratio is converted into the atomic number A of the nickel element. Ni In addition, the content ratio (mass %) of the metal element M is divided by the atomic weight of the metal element M (118.7 for tin and 65.4 for zinc), and the content ratio is converted into the atomic number A of the metal element M. M Then, calculate the number of atoms of the metal element M relative to the number of atoms of the nickel element A. Ni The atomic number A of the metal element M M The ratio (A M / (A Ni +A M )×100), find the value of Y above.
[0035] As a result of the research conducted by the inventors of the present invention, it was found that the relationship between the value of X and the value of Y affects the sintering resistance of nickel particles. Specifically, it was found that by setting the value of X / Y to 1.5 to 30, the temperature at which the nickel particles begin to shrink by sintering increases, that is, the sintering resistance becomes higher. When the nickel particles of the present invention with high sintering resistance are used to manufacture, for example, MLCC, in the firing process as one of the manufacturing processes, the temperature at which the internal electrode shrinks by sintering the nickel particles can be made as close as possible to the temperature at which the dielectric layer shrinks by sintering the dielectric particles. Reducing the difference in the temperature at which the internal electrode and the dielectric layer shrink is advantageous from the perspective of overlapping the time at which the internal electrode and the dielectric layer shrink during the temperature rise process of the firing process. Specifically, in the firing process of MLCC, it is advantageous from the perspective of effectively preventing the occurrence of structural defects such as cracks and delamination (interlayer peeling at the interface between the internal electrode and the dielectric layer) caused by the difference in temperature and shrinkage rate between the internal electrode and the dielectric layer.
[0036] From the viewpoint of making the above advantages more significant, the value of X / Y in the nickel particles is more preferably 3.7 or more. In addition, the value of X / Y in the nickel particles is more preferably 20 or less, more preferably 15 or less, further preferably 13 or less, and further preferably 10 or less.
[0037] In the particle surface area, the value of the ratio of the number of atoms of the metal element M to the total number of atoms of the nickel element and the metal element M can be constant or variable in the depth direction. In the case where the value of the above ratio is not constant in the depth direction, the value of the above ratio can also be reduced continuously or stepwise from the surface of the nickel particle toward the center. In particular, when the area from the outermost surface of the nickel particle to the sputtering depth of 20nm in terms of SiO2 is measured by XPS, the value of the above ratio decreases from the outermost surface toward the sputtering depth of 20nm, which is preferred from the perspective of further improving the sintering resistance of the nickel particle. In this case, when the maximum value of the above ratio in the area from the outermost surface of the nickel particle to the sputtering depth of 5nm is set to X, and the maximum value of the above ratio at the sputtering depth of 20nm is set to X1, the value of X / X1 is 3.0 to 15, which is preferred from the perspective of further improving the sintering resistance of the nickel particle. From the same point of view, the value of X / X1 is more preferably 3.8 or more, and more preferably 4.3 or more. Furthermore, the value of X / X1 is more preferably 10 or less, more preferably 7.8 or less, and further preferably 6.1 or less. The method for measuring X1 will be described in the examples described below.
[0038] From the viewpoint of further improving the sintering resistance of the nickel particles, the value of X1 itself is preferably 0.2 to 10, more preferably 0.5 to 6, even more preferably 0.7 to 4.1, and even more preferably 1.7 to 4.1.
[0039] The cumulative particle size D when the cumulative number of nickel particles in the present invention is 50% by number is 50 The value of is preferably 20 nm to 200 nm. In other words, the nickel particles of the present invention are preferably fine particles. 50 In this range, when the nickel particles of the present invention are used as internal electrodes of various applications, such as MLCC, there is an advantage that short circuits between the internal electrodes are less likely to occur. From the viewpoint of making this advantage more significant, the particle size D of the nickel particles is 50 The particle size D of the nickel particles is more preferably 20 nm to 170 nm, more preferably 20 nm to 150 nm, further preferably 40 nm to 150 nm, and further preferably 40 nm to 100 nm. 50 The nickel particles are measured by observing them with a scanning electron microscope (SEM). Specifically, the nickel particles are photographed by SEM at a magnification of 50,000 times, and the area of the photographed nickel particles is obtained. The equivalent circle diameter is calculated from the area. Based on the calculated equivalent circle diameter, the particle size distribution is obtained. The particle size distribution is obtained by taking the equivalent circle diameter on the horizontal axis of the graph and the number frequency on the vertical axis. In the particle size distribution curve obtained by such operation, the number cumulative particle size when the cumulative number is 50% is defined as D 50 .
[0040] When obtaining the above-mentioned "particle size distribution curve", the equivalent circle diameter is calculated for more than 5000 nickel particles. For the calculation of the equivalent circle diameter, image analysis particle size distribution measurement software (Mac-View manufactured by MOUNTECH Co., Ltd.) is used. The smallest unit of the nickel particle as the observation object is determined by whether the particle interface confirmed by an independent particle is observed using SEM. Therefore, even if an agglomerate containing multiple particles is observed, when a particle interface is observed in the agglomerate, the area delimited by the particle interface is identified as one particle.
[0041] The nickel particles of the present invention are preferably not only microparticles but also have a small proportion of coarse particles. When the nickel particles of the present invention are used for internal electrodes of MLCC, for example, the presence of coarse particles may cause a short circuit between the internal electrodes. By reducing the proportion of coarse particles in the nickel particles, the short circuit can be effectively prevented. From this point of view, in the nickel particles of the present invention, D 50The abundance ratio of particles having a particle size 1.5 times or more of the above (hereinafter also referred to as “abundance ratio of coarse particles”) is preferably 0.5% by number or less, more preferably 0.3% by number or less, and further preferably 0.1% by number or less.
[0042] The closer the proportion of coarse particles is to 0%, the more effective it is in preventing the occurrence of short circuits between internal electrodes. However, as low as the proportion of coarse particles is about 0.01%, the occurrence of short circuits between internal electrodes can be effectively prevented.
[0043] As the size of coarse particles, a particle size of D 50 The reason for the particle size of the particles being 1.5 times or more is that the inventors of the present invention have found that: 50 When the particle size is 1.5 times or more, the surface of the conductive film becomes rough when the conductive film is formed, which is closely related to the occurrence of short circuits between the internal electrodes of the MLCC.
[0044] The nickel particles of the present invention preferably have a low proportion of microparticles and coarse particles and a particle size as uniform as possible. In other words, the particle size distribution curve is preferably sharp. The sharpness of the particle size distribution curve can be evaluated by the coefficient of variation of the particle size. The coefficient of variation is calculated by (σ / D when the standard deviation of the particle size in the particle size distribution is set to σ (nm) 50 )×100(%). The value of the coefficient of variation of the nickel particles of the present invention is preferably 14% or less from the viewpoint of reducing the surface roughness of the conductive film formed by the nickel particles. From the viewpoint of further reducing the surface roughness of the conductive film, the coefficient of variation is more preferably 13% or less, and further preferably 12% or less.
[0045] The closer the coefficient of variation is to 0%, the more it contributes to reducing the surface roughness of the conductive film. However, when the coefficient of variation is as low as about 8%, the surface roughness of the conductive film can be reduced to a sufficiently satisfactory level.
[0046] The nickel particles of the present invention preferably have high nickel crystallinity. High nickel crystallinity means that the temperature at which the nickel particles of the present invention begin to shrink during sintering rises. In other words, high nickel crystallinity means that the nickel particles exhibit high sintering resistance as described above.
[0047] The crystallinity of nickel is determined by the crystallite size Cs (nm) relative to the particle size D 50 The ratio of (nm) is Cs / D 50 This method is often used in the field of metal powder technology. 50 The larger the value of Cs / D is, the higher the crystallinity of nickel can be evaluated. From this viewpoint, in the nickel particles of the present invention, Cs / D 50The value of is preferably 0.3 or more, more preferably 0.34 or more, and further preferably 0.37 or more.
[0048] Cs / D 50 The larger the value of Cs / D, the higher the temperature at which nickel particles begin to shrink during sintering. However, in the present invention, as long as Cs / D 50 The value of Cs / D is preferably 0.6 or less, which can sufficiently increase the temperature. From this point of view, 50 The value of is more preferably 0.55 or less, and further preferably 0.52 or less.
[0049] The value of the crystallite size Cs itself is preferably 15 nm to 70 nm, more preferably 18 nm to 70 nm, and even more preferably 20 nm to 70 nm, from the viewpoint of sufficiently raising the temperature at which the nickel particles begin to shrink during sintering.
[0050] As a method for measuring the crystallite size, various methods are known in the technical field of metal powders, but the crystallite size in this specification refers to a value obtained by measuring by the WPPF (whole powder pattern fitting) method. As a method for measuring the crystallite size, in addition to the WPPF method, the Scherrer method is also known, but when the degree of crystal distortion is large, the value of the crystallite size obtained based on the Scherrer method becomes unreliable, so the WPPF method with less concerns as described above is adopted in the present invention.
[0051] The details of the method for measuring the crystallite size of nickel by the WPPF method will be described in the examples described later.
[0052] The nickel particles of the present invention preferably do not excessively increase resistance. When such nickel particles are used, for example, as internal electrodes of MLCC, the performance of the MLCC can be further improved. Therefore, in order not to excessively increase resistance, it is preferred to control the crystal structure of the nickel particles in such a way that the pure nickel component in the nickel particles having a surface region containing a nickel / metal M alloy increases. From this viewpoint, in the nickel particles of the present invention, the a-axis length of the crystal lattice in the crystal structure of nickel is preferably More preferably More preferably
[0053] The a-axis length of the crystal lattice in the crystal structure of the nickel particles can be measured by an X-ray diffraction apparatus using CuKα1 rays as described in the examples below. The analysis can be obtained by the WPPF method as described in the examples below.
[0054] The crystallite size and the a-axis length of the crystal lattice in the nickel crystal structure of the present invention are achieved, for example, by adjusting the ratio of the metal element M contained in the surface region of the nickel particles and reducing the thickness of the surface region of the nickel particles containing the nickel / metal M alloy. In addition to or in lieu of this, it can also be achieved by appropriately adjusting the conditions in the method for producing the nickel particles described below.
[0055] The degree of sintering resistance of the nickel particles of the present invention can be evaluated by thermomechanical analysis (TMA) with the nickel particles as the object. In the present invention, the temperature at which the TMA shrinkage (%) becomes 5% based on room temperature (25°C) is defined as the shrinkage start temperature. The fact that the temperature is above 500°C is preferred from the perspective of further improving the sintering resistance of the nickel particles. From the perspective of making this advantage more significant, it is more preferably above 530°C, more preferably above 550°C, and more preferably above 570°C.
[0056] Next, a preferred method for producing the nickel particles of the present invention is described. In this production method, the nickel particles are produced by the so-called polyol method. The polyol method refers to a method using a polyol as a solvent that also serves as a reducing agent. In the polyol method, a reduction reaction to a nickel mother particle is generated by heating in a state where a chemical species of nickel exists in the polyol, and a compound of a metal element M is mixed before the end of the reduction reaction, and further heating is performed to generate a reduction reaction to the metal M, and a surface region containing a nickel / metal M alloy is formed on the nickel mother particle.
[0057] In the present manufacturing method, it is preferred to use nickel hydroxide as a chemical species of nickel for generating nickel particles from the viewpoint of smoothly obtaining the target nickel particles. Nickel hydroxide is added to a mixed solution containing a polyol, polyvinyl pyrrolidone (hereinafter also referred to as "PVP") and polyethyleneimine (hereinafter also referred to as "PEI"). From the viewpoint of operability, it is preferred to use nickel hydroxide having a particle-like form as the nickel hydroxide.
[0058] The polyol contained in the mixed liquid serves as a solvent as described above and also serves as a reducing agent for nickel hydroxide.
[0059] As the polyol, for example, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 1,2-propylene glycol, dipropylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,5-pentanediol and polyethylene glycol can be used. These polyols can be used alone or in combination of two or more. Ethylene glycol among these polyols has a high reduction performance because the proportion of hydroxyl groups relative to the molecular weight is large, and it is liquid at room temperature and has excellent operability, so it is preferred.
[0060] If the usage amount of polyol is considered from the viewpoint of using it as a reducing agent, it is only necessary to adjust it appropriately according to the amount of nickel hydroxide in the mixed solution, so there is no need to set special restrictions. On the other hand, when it is desired to function as a solvent, since the properties of the mixed solution change according to the concentration of the polyol in the mixed solution, there is a certain appropriate concentration range. From this viewpoint, the concentration of the polyol in the mixed solution is preferably set to a range of 50 mass % to 99.8 mass %.
[0061] PVP is used as a dispersant for nickel hydroxide. PVP is preferred because it is effective as a dispersant and can make the particle size distribution of the nickel particles generated by reduction sharp. The molecular weight of these PVPs can be appropriately adjusted according to the degree of their water solubility and dispersibility. The amount of PVP in the mixed solution is preferably set to 0.01 to 30 parts by mass relative to 100 parts by mass of nickel converted into nickel hydroxide. By setting it to this range, the dispersion effect can be fully demonstrated without excessively increasing the viscosity of the mixed solution.
[0062] PEI has the following effects: during the period of nickel nuclei being generated in the mixed solution, the number of nickel ions in the mixed solution is reduced, so that nuclei generation and nuclei growth do not proceed simultaneously. The reasons are as follows: (a) PEI has non-covalent electron pairs that interact with nickel ions and can coordinately bond with nickel ions; (b) PEI has a large amount of the above non-covalent electron pairs; and (c) PEI has hydrogen bonding sites that can interact with the surface of nickel hydroxide that exists in an undissolved state in the mixed solution.
[0063] By having PEI in the mixed solution, the nucleation of nickel and the growth of the generated nuclei can be performed in sequence. As a result, nickel particles with uniform particle size can be obtained smoothly. In contrast, in the manufacture of nickel particles based on reduction in the past, since nucleation and nucleus growth occur simultaneously, coarse particles are easily generated, and the particle size is easily uneven.
[0064] From the above viewpoints, it is advantageous to use branched PEI as PEI rather than linear PEI. From the same viewpoint, it is also preferred to use PEI with a number average molecular weight of 600 to 10,000, particularly preferably PEI with a number average molecular weight of 800 to 5,000, and particularly preferably PEI with a number average molecular weight of 1,000 to 3,000.
[0065] Particularly in this manufacturing method, by setting the ratio of PVP to PEI contained in the mixed solution to a specific range, it is reliable to sequentially perform the nucleation and nucleus growth of nickel. Specifically, relative to 1 mass part of PEI, preferably 30 mass parts to 200 mass parts of PVP are used, more preferably 40 mass parts to 150 mass parts of PVP are used, and further preferably 50 mass parts to 130 mass parts of PVP are used.
[0066] The amount of PEI in the mixed solution is appropriately set according to the amount of PVP, provided that the ratio of PVP to PEI satisfies the above-mentioned range.
[0067] It is also possible to make the mixed solution contain a noble metal catalyst. Thus, fine core particles of the noble metal are generated in the initial stage of reduction, and nickel is smoothly reduced with the core particles as the starting point. As a noble metal catalyst, for example, a noble metal compound such as a water-soluble salt of a noble metal can be used. As examples of water-soluble salts of noble metals, water-soluble salts of palladium, silver, platinum, gold, etc. can be cited. In the case of using palladium as a noble metal, for example, palladium chloride, palladium nitrate, palladium acetate, ammonium palladium chloride, etc. can be used. In the case of using silver, for example, silver nitrate, silver lactate, silver oxide, silver sulfate, silver cyclohexanoate, silver acetate, etc. can be used. In the case of using platinum, for example, chloroplatinic acid, potassium chloroplatinate, sodium chloroplatinate, etc. can be used. In the case of using gold, for example, chloroauric acid, sodium chloroaurate, etc. can be used. Among them, palladium nitrate, palladium acetate, silver nitrate and silver acetate are preferably used because they are cheap and economical. The noble metal catalyst can be added in the form of the above-mentioned compound or in the form of an aqueous solution obtained by dissolving the compound in water. The amount of the noble metal catalyst contained in the mixed liquid is preferably 0.01 to 5 parts by mass, particularly preferably 0.01 to 1 part by mass, relative to 100 parts by mass of nickel hydroxide converted to nickel.
[0068] The mixed solution containing the above components is heated while being stirred to reduce the nickel hydroxide. The heating temperature varies depending on the type of polyol used, but the nickel hydroxide can be smoothly reduced to the nickel mother particle by heating at preferably 150° C. to 200° C., more preferably 170° C. to 200° C., and further preferably 190° C. to 200° C. under atmospheric pressure.
[0069] Next, before the reduction reaction of nickel hydroxide is completed, a compound of the metal element M is mixed into the above-mentioned mixed solution. In other words, the compound of the metal element M is mixed into the above-mentioned mixed solution in a state where a part of the nickel hydroxide remains. The so-called "before the reduction reaction of nickel hydroxide is completed" here means before the nickel hydroxide is reduced by 80 mol% or more relative to the amount of nickel hydroxide input. In the case where the metal element M is tin, from the viewpoint of smoothly forming a surface region containing a nickel / metal M alloy on the nickel mother particle in the reduction reaction of the compound of the metal element M described later, as the compound, it is preferred to use at least one selected from sodium stannate trihydrate, tin chloride (II), and tin chloride (IV), and sodium stannate trihydrate is particularly preferred. In addition, in the case where the metal element M is zinc, from the same viewpoint as above, as the compound, it is preferred to use at least one selected from zinc sulfate, zinc nitrate, zinc chloride, zinc hydroxide and zinc oxide, and zinc hydroxide is particularly preferred.
[0070] When the metal element M is tin, from the viewpoint of smoothly forming a surface region of an alloy containing nickel and tin on the nickel mother particle, it is preferred that the amount of the tin compound in the mixed solution, converted into tin, is set to 0.016 mass parts or more, more preferably 0.003 mass parts or more, more preferably 0.004 mass parts or more, and further preferably 0.01 mass parts or more, relative to 1 mass part of the nickel amount put in. In addition, it is preferred that the amount of the tin compound in the mixed solution, converted into tin, is set to 0.12 mass parts or less, and more preferably 0.06 mass parts or less, relative to 1 mass part of the nickel amount put in.
[0071] When the metal element M is zinc, from the viewpoint of smoothly forming a surface region of an alloy containing nickel and zinc on the nickel mother particle, it is preferred that the amount of the zinc compound in the mixed solution, converted into zinc, is set to 0.016 mass parts or more, more preferably 0.002 mass parts or more, more preferably 0.004 mass parts or more, and further preferably 0.005 mass parts or more, relative to 1 mass part of the nickel amount put in. In addition, it is preferred that the amount of the zinc compound in the mixed solution, converted into zinc, is set to 0.12 mass parts or less, more preferably 0.070 mass parts or less, and further preferably 0.034 mass parts or less, relative to 1 mass part of the nickel amount put in.
[0072] Next, the mixed solution containing the compound of the above metal element M is heated while stirring to reduce the nickel hydroxide and the compound in the mixed solution. Through the reduction reaction, the nickel hydroxide remaining in the mixed solution is reduced to nickel, and when the metal element M is tin, the compound of the metal element M is reduced to tin, and when the metal element M is zinc, the compound of the metal element M is reduced to zinc. In the reduction reaction, by reducing the nickel hydroxide and the compound of the metal element M at the same time, a surface region containing a nickel / metal M alloy in which the nickel element and the metal M are homogeneously solid-dissolved is formed on the surface of the nickel mother particle. It should be noted that as long as the effect of the present invention can be exerted, a part of the metal element M is allowed to exist in the state of a single substance of the metal element M, the state of a compound of the metal element M, or a combination of two or more of them.
[0073] The heating temperature of the mixed solution varies depending on the types of the polyol and the compound of the metal element M used, but is preferably 150° C. to 200° C., more preferably 170° C. to 200° C., and further preferably 190° C. to 200° C. at atmospheric pressure. By setting the heating temperature within this range, the nickel hydroxide and the compound of the metal element M can be reduced simultaneously, and a surface region containing a nickel / metal M alloy can be smoothly formed on the surface of the nickel mother particle.
[0074] Thereafter, if necessary, the polyol in the obtained dispersion of nickel particles is replaced with water, and then the replaced water is replaced with methanol to wash the nickel particles, followed by vacuum drying. The nickel particles of the present invention can be produced in this manner.
[0075] In the case of manufacturing nickel particles containing metal element M, a raw material of metal element M can be added to the nickel raw material to perform PVD method or CVD method. The nickel particles in this case become nickel / metal M alloys formed in their entirety. However, in the case of wanting to improve the sintering resistance of the nickel particles, the content of metal element M, i.e., tin and / or zinc, in the nickel particles as a whole becomes too high, and as a result, there is a problem of increased resistance. In addition, since the particle size of the nickel particles becomes uneven, the surface of the conductive film becomes rough when the nickel particles are used to form a conductive film, and there is a problem of becoming one of the causes of short circuits between the internal electrodes of the MLCC. In addition, as another method for manufacturing nickel particles containing metal element M, as described in Patent Document 2, there is a method of adding a compound of metal element M after reducing the entire amount of nickel hydroxide. In this case, a layer of a single substance of metal element M, i.e., tin and / or zinc, having a melting point lower than nickel, is formed on the surface of the nickel particles. However, the sintering resistance of the nickel particles is caused by the surface of the particles being formed by a layer of a single substance of tin and / or zinc and will not become higher. In contrast, the nickel particles of the present invention, which include a nickel matrix particle and a nickel / metal M alloy disposed on the surface thereof, can improve sintering resistance without excessively increasing resistance. Furthermore, if a conductive film is formed using the nickel particles of the present invention, the surface of the conductive film can be made smooth. For these reasons, as described above, it is preferred that the nickel hydroxide and the compound of the metal element M are simultaneously reduced in a state where a portion of the nickel hydroxide remains to produce the nickel particles.
[0076] The nickel particles produced by the above method are fine particles with uniform particle size, but can be used in various fields by utilizing the feature that the nickel particles have a surface region containing a nickel / metal M alloy on their surface. In particular, they can be suitably used for forming internal electrodes of MLCCs.
[0077] The present invention has been described above based on its preferred embodiment, but the present invention is not limited to the above embodiment. For example, the nickel particles of the present invention have a surface region containing a nickel / tin alloy on their surface, but the inventors of the present invention have studied and found that even when the nickel particles are manufactured using zinc instead of tin, the above advantages can be fully utilized. In other words, the inventors of the present invention have studied and found that the above advantages can be fully utilized by the following nickel particles, which have a surface region containing a nickel / zinc alloy, and the content of zinc relative to the entire nickel particle is within a specified range, and when the region from the outermost surface to the sputtering depth of 5nm in terms of SiO2 is measured by X-ray photoelectron spectroscopy in the depth direction of the nickel particle, the maximum value of the ratio of the number of atoms of zinc to the total number of atoms of nickel and zinc is set to X2, and when the nickel particles are measured by ICP emission spectrometry, the ratio of the number of atoms of zinc to the total number of atoms of nickel and zinc is set to Y1, and the value of X2 / Y1 is within a specified range. Such nickel particles can be easily produced by using zinc instead of tin in the preferred method for producing nickel particles of the present invention. Furthermore, when zinc is used together with tin in the above-mentioned production method to produce nickel particles having a surface region containing a nickel / tin / zinc alloy, the above-mentioned advantages can also be fully utilized.
[0078] As mentioned above, although this invention was demonstrated based on the preferred embodiment, this invention is not limited to the said embodiment.
[0079] With respect to the above-mentioned embodiment, the following nickel particles and a method for producing the same are further disclosed.
[0080] [1] A nickel particle having a surface region comprising an alloy of nickel and a metal element M,
[0081] The metal element M is at least one selected from tin and zinc,
[0082] The content of the metal element M relative to the total mass of the nickel particles is 0.16 mass % to 11.4 mass %,
[0083] When measuring the area from the outermost surface to the sputtering depth of 5 nm in terms of SiO2 in the depth direction of the above-mentioned nickel particles by X-ray photoelectron spectroscopy, in this area, the maximum value of the ratio of the number of atoms of the metal element M to the total number of atoms of the nickel element and the metal element M is set to X (at%), and when the above-mentioned nickel particles are measured by ICP emission spectroscopy, when the ratio of the number of atoms of the metal element M to the total number of atoms of the nickel element and the metal element M is set to Y (at%), the value of X / Y is 1.5 to 30.
[0084] [2] The nickel particles according to [1], wherein in a particle size distribution obtained based on an equivalent circle diameter calculated by measurement using a scanning electron microscope, the cumulative particle size at a cumulative number of 50% is set as D 50 When D 50 20nm~200nm,
[0085] When the standard deviation of the particle size in the above particle size distribution is set to σ (nm), the coefficient of variation (σ / D 50 The value of ) (%) is less than 14%.
[0086] Coefficient of variation (%) = (σ / D 50 )×100
[0087] [3] The nickel particles according to [1] or [2], wherein in a particle size distribution obtained based on an equivalent circle diameter calculated by measurement using a scanning electron microscope, the cumulative particle size at a cumulative number of 50% is set as D 50 When D 50 The proportion of particles having a particle size 1.5 times or more of the above-mentioned particle size is 0.5% by number or less.
[0088] [4] The nickel particles according to any one of [1] to [3], wherein in a particle size distribution obtained based on an equivalent circle diameter calculated by measurement using a scanning electron microscope, the cumulative particle size at a cumulative number of 50% is set as D 50 , when the crystallite size measured by the WPPF method is set to Cs (nm), Cs / D 50 The value is 0.3~0.6.
[0089] [5] A method for producing nickel particles, comprising heating a mixed solution containing nickel hydroxide particles, a polyol, polyvinyl pyrrolidone and polyethyleneimine to produce nickel particles,
[0090] 30 to 200 parts by mass of polyvinyl pyrrolidone is used per 1 part by mass of polyethyleneimine.
[0091] The nickel hydroxide particles are reduced to nickel mother particles by the heating.
[0092] The mixed solution is mixed with a compound of a metal element M while a portion of the nickel hydroxide particles remain, and the compound is reduced to metal M, thereby forming a surface region of an alloy containing nickel and the metal element M on the nickel mother particle.
[0093] The metal element M is at least one selected from tin and zinc.
[0094] [6] A multilayer ceramic capacitor using the nickel particles described in any one of [1] to [4] in internal electrodes.
[0095] Example
[0096] The present invention will be described in more detail below by way of examples. However, the scope of the present invention is not limited to the examples. Unless otherwise specified, "%" means "mass %".
[0097] [Example 1]
[0098] In a 500ml beaker, 445g of ethylene glycol, 64g of nickel hydroxide particles, 12g of polyvinyl pyrrolidone, 0.14g of polyethylene imine and 0.13ml of palladium nitrate aqueous solution (concentration: 100g / l) were added to prepare a mixed solution. Polyethylene imine is a branched polyethylene imine with a number average molecular weight of 1800. The mixed solution was heated while stirring and subjected to a reduction reaction at 198°C for 5 hours under atmospheric pressure. At this moment, the reduction of nickel hydroxide was 80mol% relative to the amount of nickel hydroxide added. Then, 0.5g of sodium stannate trihydrate was added and the reduction reaction was further carried out at 198°C for 10 hours under atmospheric pressure. The heating was stopped to terminate the reduction and the mixture was cooled to room temperature naturally. By operating in this way, a large amount of nickel particles were obtained.
[0099] A magnet was placed at the bottom of the beaker containing the obtained nickel particle dispersion to attract the nickel particles to the magnet. In this state, the supernatant of the dispersion was removed.
[0100] After removing the magnet from the bottom of the beaker, 50 g of pure water was added and the dispersion was stirred for 10 minutes. Afterwards, a magnet was placed again at the bottom of the beaker to attract the nickel particles to the magnet. In this state, the supernatant of the above dispersion was removed. This series of operations was repeated 5 times.
[0101] Next, 50 g of methanol was added and the dispersion was stirred for 10 minutes. The removal of the supernatant was repeated three times using a magnet to replace the solvent in the dispersion with methanol. Thereafter, vacuum drying was performed at 80° C. to obtain nickel particles.
[0102] [Examples 2 to 6]
[0103] The addition amount of the aqueous palladium nitrate solution and the addition amount of sodium stannate trihydrate, and the time from the start of heating the mixed solution to the addition of sodium stannate trihydrate to the mixed solution were set as shown in Table 1. Except for these, the same operation as in Example 1 was carried out to obtain nickel particles.
[0104] [Examples 7 to 12]
[0105] Zinc hydroxide was added instead of sodium stannate trihydrate. The addition amount of the aqueous palladium nitrate solution and the addition amount of zinc hydroxide were set as shown in Table 1. Except for these, the same operation as in Example 1 was carried out to obtain nickel particles.
[0106] [Comparative Example 1]
[0107] In a 500 ml beaker, add 445 g of ethylene glycol, 64 g of nickel hydroxide particles, 8 g of polyvinyl pyrrolidone, 0.14 g of polyethylene imine and 0.13 ml of palladium nitrate aqueous solution (concentration: 100 g / l) to prepare a mixed solution. Polyethylene imine is a branched polyethylene imine with a number average molecular weight of 1800. The mixed solution is heated while stirring and subjected to a reduction reaction at 198°C for 6.5 hours. Stop heating to terminate the reduction and let it cool naturally to room temperature. By operating like this, a large amount of nickel particles are obtained.
[0108] A magnet was placed at the bottom of the beaker containing the obtained dispersion of nickel particles to attract the nickel particles to the magnet. In this state, the supernatant of the dispersion was removed.
[0109] After removing the magnet from the bottom of the beaker, 50 g of pure water was added and the dispersion was stirred for 10 minutes. Afterwards, a magnet was placed again at the bottom of the beaker to attract the nickel particles to the magnet. In this state, the supernatant of the above dispersion was removed. This series of operations was repeated 5 times.
[0110] Next, 50 g of methanol was added and the dispersion was stirred for 10 minutes. The removal of the supernatant was repeated three times using a magnet to replace the solvent in the dispersion with methanol. Thereafter, vacuum drying was performed at 80° C. to obtain a powder of nickel particles.
[0111] [Comparative Example 2]
[0112] Nickel particles were obtained in the same manner as in Example 1 except that sodium stannate trihydrate was added before the reduction reaction of nickel hydroxide.
[0113] [Comparative Example 3]
[0114] In a 500 ml beaker, add 445 g of ethylene glycol, 64 g of nickel hydroxide particles, 8 g of polyvinyl pyrrolidone, 0.14 g of polyethylene imine and 0.13 ml of palladium nitrate aqueous solution (concentration: 100 g / l) to prepare a mixed solution. Polyethylene imine is a branched polyethylene imine with a number average molecular weight of 1800. The mixed solution is heated while stirring and subjected to a reduction reaction at 198°C for 6.5 hours. Stop heating to terminate the reduction and let it cool naturally to room temperature. By operating like this, a large amount of nickel particles are obtained.
[0115] A magnet was placed at the bottom of the beaker containing the obtained nickel particle dispersion to attract the nickel particles to the magnet. In this state, the supernatant of the dispersion was removed.
[0116] After removing the magnet from the bottom of the beaker, 50 g of pure water was added and the dispersion was stirred for 10 minutes. Afterwards, a magnet was placed again at the bottom of the beaker to attract the nickel particles to the magnet. In this state, the supernatant of the above dispersion was removed. This series of operations was repeated 5 times.
[0117] To this dispersion, 300 g of pure water and hydrazine monohydrate were added and the temperature was raised to 60° C., and then 1 g of sodium stannate trihydrate was added and stirred for 5 hours to perform surface treatment on the nickel particles with tin.
[0118] A magnet was placed at the bottom of the beaker containing the obtained nickel particle dispersion to attract the nickel particles to the magnet. In this state, the supernatant of the dispersion was removed.
[0119] After removing the magnet from the bottom of the beaker, 50 g of pure water was added and the dispersion was stirred for 10 minutes. Afterwards, a magnet was placed again at the bottom of the beaker to attract the nickel particles to the magnet. In this state, the supernatant of the above dispersion was removed. This series of operations was repeated 5 times.
[0120] Next, 50 g of methanol was added and the dispersion was stirred for 10 minutes. The removal of the supernatant was repeated three times by using a magnet, and the solvent in the dispersion was replaced with methanol. After that, vacuum drying was performed at 80° C. to obtain a powder of nickel particles surface-treated with tin. As described in [Evaluation 1] described later, it was confirmed that the surface region of the nickel particles did not contain an alloy of nickel and tin, and a tin surface layer was formed.
[0121] 〔Evaluation 1〕
[0122] The value of X and the value of X1 were determined for the nickel particles obtained in Examples 1 to 12 and Comparative Examples 1 to 3 by the following XPS analysis method.
[0123] In addition, the contents of tin element and zinc element relative to the entire nickel particles and the value of Y were determined by ICP emission spectroscopy.
[0124] In addition, the particle size distribution was measured by the above method to obtain the particle size D 50 , the proportion of coarse particles and the coefficient of variation.
[0125] In addition, the a-axis length and crystallite size Cs of nickel based on the WPPF method were obtained by the following method.
[0126] In addition, it was confirmed by the above-mentioned method whether the surface region of the nickel particles contained an alloy of nickel and tin, and whether the surface region of the nickel particles contained an alloy of nickel and zinc.
[0127] The above results are shown in the following Table 1. In addition, SEM images of the nickel particles obtained in Example 3 and Comparative Example 2 are shown in Figure 1 and 2 middle.
[0128] [X-ray photoelectron spectroscopy (XPS) measurement]
[0129] For the XPS test sample, a sample obtained by forming nickel particles into granules using a press was used. Specifically, about 10 mg of the particle sample was added to an aluminum container having a size of φ5.2 mm and a height of 2.5 mm. Next, a press (AS ONE, model: 1-312-01) and an adapter (model: 1-312-03) were used to pressurize the aluminum container with a specified stroke (25 mm). Next, the granular formed product of the nickel particles supported by the aluminum container was taken out.
[0130] The obtained pellet molded product was subjected to outermost surface measurement and depth measurement from the sample surface toward the inside by sputtering with Ar simple ions. The measurement conditions were as follows.
[0131] ·Measurement device: VersaProbe III manufactured by ULVAC-PHI Co., Ltd.
[0132] ·Excitation X-ray: Monochromated Al-Kα ray (1486.7eV)
[0133] Output power: 50W
[0134] Accelerating voltage: 15kV
[0135] ·X-ray irradiation diameter: 200μmφ
[0136] X-ray scanning area: 1000μm×300μm
[0137] Detection angle: 45°
[0138] Bandpass energy: 26.0eV
[0139] Energy step: 0.1eV / step
[0140] Sputtering ion species: Ar monomer ion
[0141] Sputtering rate: 3.3nm / min (SiO2 conversion)
[0142] Sputtering interval: 20s
[0143] ·Measured element: C 1s 、Ni 2p3 Sn 3d5 、Zn 2p3
[0144] Energy correction value: C 1s CC bond and CH bond in (284.8eV)
[0145] 〔Analysis of XPS data〕
[0146] XPS data were analyzed using data analysis software ("MultiPak Ver9.9" manufactured by ULVAC-PHI Inc.) Shirley was used as the background mode.
[0147] [Value of X]
[0148] In Examples 1 to 6, Sn 3d5 The atomic number of Ni 2p3 With Sn 3d5 The total atomic ratio of the two elements is set as X (at%). In Examples 7 to 12, Zn 2p3 The atomic number of Ni 2p3 With Zn 2p3 The ratio of the total number of atoms of the two elements is set to X (at %).
[0149] 〔Measurement of a-axis length and crystallite size Cs〕
[0150] The a-axis length and the crystallite size Cs of the nickel particles obtained in Examples and Comparative Examples were calculated using the WPPF method from the diffraction peak derived from nickel obtained by X-ray diffraction measurement.
[0151] Device name SmartLab (9KW): Made by Rigaku Corporation
[0152] <Device Configuration>
[0153] wavelength
[0154] Target: Cu
[0155] Wavelength type: Kα1
[0156] Kα1:
[0157] Kα2:
[0158] Kβ:
[0159] Kα12 intensity ratio: 0.4970
[0160] Horizontal polarization rate: 0.500
[0161] Diffraction device
[0162] Goniometer: SmartLab
[0163] Accessory base: Z-axis stage separate
[0164] Accessories: ASC6-Reflector
[0165] <Measurement Conditions>
[0166] Optical system properties: Concentration method
[0167] CBO selects slit: BB
[0168] ·Entrance parallel slit: Soller_slit_5.0deg
[0169] Entrance slit: 2 / 3deg
[0170] Length limit slit: 10.0mm
[0171] · Light receiving slit 1: 20.000mm
[0172] · Light receiving parallel slit: Soller_slit_5.0deg
[0173] · Light receiving slit 2: 20.000mm
[0174] Attenuator: On
[0175] Detector: D / teX Ultra250
[0176] Scanning axis: 2θ / θ
[0177] Scan mode: continuous
[0178] Scanning range: 5.0000~140.0000deg
[0179] Step size: 0.0100deg
[0180] Scanning speed / measurement time: 2.015572deg / min
[0181] Number of data points: 13501
[0182] Tube voltage: 45kV
[0183] Tube current: 200mA
[0184] HV: 0.00
[0185] <Preparation of Specimen for X-ray Diffraction>
[0186] Cover the nickel particles to be measured on the measurement holder, and smooth them using a glass plate in such a way that the thickness of the layer formed by the nickel particles becomes 0.5 mm and the measurement surface becomes smooth.
[0187] Using the X-ray diffraction pattern obtained under the above measurement conditions, perform analysis using analysis software under the following conditions. In the analysis, correction was performed using data obtained from a standard substance, lanthanum hexaboride powder (SRM660 series), provided by the National Institute of Standards and Technology (NIST) of the United States. The a-axis length and the microcrystalline size Cs were calculated using the WPPF method.
[0188] <Analysis Conditions for Measurement Data>
[0189] · Analysis software: PDXL2 manufactured by Rigaku
[0190] · Analysis method: WPPF method
[0191] · Data processing: Automatic profile processing
[0192] (Rigaku Corporation PDXL User's Guide p.305)
[0193] 〔Evaluation 2〕
[0194] For the nickel particles obtained in Examples 1 to 12 and Comparative Examples 1 to 3, the shrinkage start temperature, the resistivity of the sintered film containing the nickel particles, and the surface roughness Rz of the nickel particles were measured by the following methods. The above results are shown in Table 1 below.
[0195] 〔Measurement of Shrinkage Start Temperature〕
[0196] As the measurement device for TMA, TMA / SS6000 manufactured by Seiko Instruments Inc. was used. 0.2 to 0.3 g of nickel particles were placed in a stainless steel mold container with a diameter of φ5.0 mm, and compression molding was performed by applying a pressure of 92 MPa to the nickel particles to produce pellets. The pellet length of the obtained pellets was measured and used as the measurement object specimen. It was set in the measurement device, and the specimen was heated at 5 °C / min in an atmosphere of a load of 49 mN and 1 vol% hydrogen / 99 vol% nitrogen. The measurement was started from room temperature (25 °C), and a chart showing the relationship between temperature and shrinkage rate (%) was obtained. The shrinkage start temperature was determined from the obtained chart.
[0197] 〔Measurement of Resistivity〕
[0198] Dissolve 0.1 g of ethyl cellulose in 4 g of terpineol, and then add 5 g of nickel particles to obtain a mixture. Mix this mixture using a planetary mixer ("Avatori Renta-ro (registered trademark)" manufactured by THINKY Corporation). Then, pass this mixture through a three-roll mill 4 times to crush it. The gap of the three-roll mill is set to 8 μm. By operating in this way, a coating solution is obtained.
[0199] Apply this coating solution onto an alumina substrate to form a coating film. The thickness of the coating film is 30 μm. Sinter this coating film in an atmosphere of 1 vol% hydrogen / 99 vol% nitrogen at 800 °C for 60 minutes to obtain a sintered film. For this sintered film, use Loresta MCP-T600 manufactured by Mitsubishi Analytech as a four-probe resistivity measurement device to measure the resistivity (Ω·cm).
[0200] [Measurement of surface roughness Rz]
[0201] Use SURFCOM 130A to measure the surface roughness Rz of the above-mentioned sintered film. The measurement conditions are set as follows: the evaluation length is 6.0 mm, and the measurement speed is 0.6 mm / s.
[0202] [Table 1]
[0203]
[0204] As shown by the results in Table 1, through XPS measurement, it was confirmed that the nickel particles obtained in Examples 1 to 6 contain tin element in the metallic state in their surface region. Furthermore, the a-axis length of the nickel particles obtained in the Examples is longer than that of the nickel particles obtained in Comparative Example 1 where no tin compound was used. From these results, it was learned that the nickel particles obtained in Examples 1 to 6 contain an alloy of nickel and tin in their surface region.
[0205] In addition, as shown by the results in Table 1, through XPS measurement, it was confirmed that the nickel particles obtained in Examples 7 to 12 contain zinc element in the metallic state in their surface region. Furthermore, the a-axis length of the nickel particles obtained in the Examples is longer than that of the nickel particles obtained in Comparative Example 1 where no zinc compound was used. From these results, it was learned that the nickel particles obtained in Examples 7 to 12 contain an alloy of nickel and zinc in their surface region.
[0206] In addition, as shown by the results in Table 1, the nickel particles obtained in Examples 1 to 12 show a higher shrinkage start temperature compared to the nickel particles obtained in Comparative Examples 1 to 3. From this, it was learned that the nickel particles obtained in Examples 1 to 12 show high sintering resistance.
[0207] In particular, as is apparent from the comparison between Examples 1 to 5 and Example 6, it is understood that the resistivity of a sintered film obtained from the nickel particles can be controlled by controlling the amount of tin contained in the nickel particles.
[0208] In addition, the surfaces of the sintered films of Examples 1 to 6, which produced nickel particles having a surface region formed with an alloy of nickel and tin, became smoother than those of Comparative Example 2, in which an alloy of nickel and tin was formed throughout the nickel particles. It is understood from these that the surface roughness of the sintered film is reduced by the nickel particles having a surface region containing an alloy of nickel and tin.
[0209] Furthermore, if the corresponding embodiment 3 Figure 1 and corresponding to Comparative Example 2 Figure 2 By comparison, it can be seen that Figure 1 The nickel particles have a uniform particle size. Figure 2 The particle size of the nickel particles is not uniform.
[0210] Industrial Applicability
[0211] According to the present invention, nickel particles having high sintering resistance can be provided without excessively increasing electrical resistance.
Claims
1. A nickel particle having a surface region comprising an alloy of nickel and a metal element M, The metal element M is at least one selected from tin and zinc, The content of the metal element M relative to the entire nickel particles is 0.16 mass % to 11.4 mass %, When measuring the region from the outermost surface to a sputtering depth of 5 nm in terms of SiO2 in the depth direction of the nickel particles by X-ray photoelectron spectroscopy, in the region, the maximum value of the ratio of the number of atoms of the metal element M to the total number of atoms of the nickel element and the metal element M is set to X in at%, and when measuring the nickel particles by ICP emission spectroscopy, the ratio of the number of atoms of the metal element M to the total number of atoms of the nickel element and the metal element M is set to Y in at%, and the value of X / Y is 1.5 to 30.
2. The nickel particles according to claim 1, wherein In the particle size distribution obtained based on the equivalent circle diameter calculated by measurement using a scanning electron microscope, the number cumulative particle diameter when the cumulative number is 50% by number is set as D 50 When D 50 20nm~200nm, When the standard deviation of the particle size in the particle size distribution is set to σ in nm, the coefficient of variation (σ / D 50 ) is less than 14%, Coefficient of variation (%) = (σ / D 50 )×100.
3. The nickel particles according to claim 1, wherein In the particle size distribution obtained based on the equivalent circle diameter calculated by measurement using a scanning electron microscope, the number cumulative particle diameter when the cumulative number is 50% by number is set as D 50 When D 50 The proportion of particles having a particle size 1.5 times or more of the above-mentioned particle size is 0.5% by number or less.
4. The nickel particles according to claim 1, wherein In the particle size distribution obtained based on the equivalent circle diameter calculated by measurement using a scanning electron microscope, the number cumulative particle diameter when the cumulative number is 50% by number is set as D 50 , when the crystallite size measured by the WPPF method is set as Cs in nm, Cs / D 50 The value is 0.3~0.
6.
5. A method for producing nickel particles, comprising heating a mixed solution containing nickel hydroxide particles, a polyol, polyvinyl pyrrolidone and polyethyleneimine to produce nickel particles, 30 to 200 parts by mass of polyvinyl pyrrolidone is used per 1 part by mass of polyethyleneimine. The nickel hydroxide particles are reduced to nickel mother particles by the heating. The mixed solution is mixed with a compound of a metal element M while a portion of the nickel hydroxide particles remain, and the compound is reduced to metal M, thereby forming a surface region of an alloy containing nickel and the metal element M on the nickel mother particle. The metal element M is at least one selected from tin and zinc. 6 . A multilayer ceramic capacitor using the nickel particles according to claim 1 in internal electrodes.
Citation Information
Patent Citations
Alkaline electroplating Zn-Ni alloy additive, electroplating solution and preparation method
CN101942684A
Nickel-coated copper powder, method for producing the same and conductive paste
JP2018141180A
Nickel particle coated with nickel hydroxide and manufacturing method thereof
TW201032920A
Nickel colloidal catalyst solution for electroless nickel or nickel alloy plating, method for electroless nickel or nickel alloy plating, and method for manufacturing nickel plated or nickel alloy substrate
TW202140852A
Nickel powder, method for producing same, conductive composition, and conductive film
WO2022137691A1